Social transfer policies and child poverty in European countries: Evaluating policy alternatives through a multiobjective programming model - González-Gallardo, Sandra; Bárcena-Martín, Elena María; Pérez-Moreno, Salvador Jesús; Luque-Gallego, Mariano (Elsevier, 2024)
Child poverty remains a significant concern across Europe and citizens regard policy interventions that effec- tively address this issue to be of utmost importance. In this work, we analyse the potential of social transfer policy alternatives to alleviate child and overall poverty simultaneously in European countries. Using a logistic regression to define the objective functions and constraints, we rely on multiobjective programming to assess key features of national social transfer systems that can minimize child and overall poverty and tend to equal both levels downwards. Taking into account the starting levels of each country, the results underline the importance of finding an adequate combination of pro-child and pro-poor targeting of social transfer policies. For most Eu- ropean countries, an increase in the level of cash benefits for children is advisable – particularly universal benefits – except in Croatia, the Netherlands, and Norway. Nonetheless, in France, Greece, Italy, Ireland, the Netherlands, and Spain, the recommended proportion of GDP allocated to universal cash benefits is lower than the proportion allocated to means-tested benefits. In this regard, our research provides an innovative approach for policymakers to optimize poverty reduction strategies by contributing valuable insights for the design and implementation of effective social transfer policies to combat child and overall poverty in European countries.
Keywords: Niños; Pobreza; Econometría - Análisis; Multiobjective programming; Econometric analysis; Child poverty; Social transfer policy